Aid and violence reduction - Anke Hoeffler (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
Although the provision of security to all their citizens is a state's fundamental duty, over 50 countries experienced armed conflict in 2021. The international development community has identified armed conflict as an impediment to development and provides considerable resources to reduce armed conflicts. However, other forms of violence, such as suicide, homicide, and assault, are vastly more prevalent and far more widely distributed across countries than armed conflict. For some time, scholars in the field of public health have been arguing for putting selfdirected and interpersonal violence higher on domestic and international policy agendas. When analysing the allocation of aid by purpose, it is obvious that donors and recipients have so far neither recognized self-directed nor interpersonal violence as a major development issue. Almost no aid is targeted at suicide prevention and less than one per cent of total official development assistance is targeted at interpersonal violence.
Keywords: O11; O15; O19; 330; aid; violence; conflict; interpersonal violence; self-directed violence